The impact of turbulence and combustion models on flames and emissions in a low swirl burner - Cellek, Mehmet Salih; Pinarbasi, Ali; Coskun, Gokhan; Demir, Usame (ELSEVIER SCI LTD, 2023)
Since natural gas fuel boilers are environmentally friendly and efficient, they are widely used in heating systems today. Improvements are continuing in the combustion efficiency and emissions of these boilers. Due to the high costs and long manufacturing times, experimental studies are progressing slowly. For this reason, studies with CFD simulations are also preferred. For realistic CFD results, it is important to correctly choose the turbulence and combustion models. This study conducted an experimental study to obtain temperature and emission measurements from a low-swirl natural gas boiler. Then, CFD simulations were made under the same conditions using the 3D model prepared for the same boiler. In simulation studies, different turbulence and combustion models were investigated. The turbulence models used in the simulations are Standard k -e, Realizable k -e, RNG k -e, and Reynolds Stress Model (RSM), respectively. Combustion models are Eddy Dissipation (ED), Finite Rate/ Eddy Dissipation (FR/ED), Eddy Dissipation Concept (EDC), Non-Premix Combustion (NPC) and Partial-Premix Combustion (PPC). When the results obtained by numerical simulations are compared with the experimental data, it is understood that the Realizable k -e turbulence model provides better convergence than other turbulence models, while PPC and ED provide better convergence in combustion models. Since the two-step chemical mechanism for natural gas used in EDC and FR/ED models neglects the formation of many intermediate products, higher NOx values were obtained than the experimental for these combustion models. Different results were obtained from the standard k -e in terms of temperature and CO2, H2O, O2, CO, NOx results than other tur-bulence models.
Keywords: Low swirl boiler; Natural gas; CFD; Turbulence model; Combustion model; PREMIXED FLAME; NATURAL-GAS; TEMPERATURE-MEASUREMENTS; RADIATION MODELS; HYDROGEN; THERMOCOUPLE; FUEL; SIMULATIONS; VALIDATION; METHANE; Energy & Fuels; Engineering